Entrepreneurship: Pelatihan Menjadi Wirausaha Kreatif & Inovatif dalam Pemanfaatan Media Sosial - Silvianevane Paramasari; Formas Juitan Lase; Aprina Jovanka Sirait; Venesa Haliza Dewi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2025)
This PKM is carried out as a form of integration of teaching, research and community service between lecturers and students. Cijayanti Village in Babakan Madang District, Sentul, West Java is the main target where this PKM is implemented. The implementing team saw that there was a talent for the skills of parents in Cijayanti Village in terms of selling, but knowledge about the use of social media for selling was still not widely understood by entrepreneurs in Cijayanti, therefore this PKM aims to provide training to develop knowledge and skills for all participants this training. This PKM is conceptualized into 2 parts, namely presentation of material and a workshop on using social media to sell digitally. One method that the implementation team uses is by distributing pre-test & post-test questionnaires as a measuring tool for increasing understanding of training participants and becomes the final result of this PKM. The results of this PKM were a significant increase in understanding between before and after participants received training, which was positive and the initial objectives of this PKM could be achieved well.